Criminal reactions to drug-using offenders: A systematic review of the effect of treatment and/or punishment on reduction of drug use and/or criminal recidivism - Tomaz, Vera; Moreira, Diana; Souza Cruz, Olga (Frontiers in Psychiatry, 2023)
The association between substance use and crime is very common, but complex. Several countries have found strategies to face drug abuse and criminality that may exist associated to it, seeking to reduce overcrowded prisons and to promote the reductions of criminal recidivism and/or substance use. Through the guidelines of PRISMA, a systematic review was conducted with the aim to explore the different criminal reactions to individuals who use substances and are involved in the criminal justice system, namely the role of treatment and/or punishment in the reduction of crime recidivism and/or drug (ab)use. After gathering the following criteria of inclusion (individuals who use substances and are involved in the criminal justice system, between 18-65 years old, regardless of gender; consumers of licit/illicit psychoactive substances; without psychopathology not related with use/abuse of drugs; treatment programs; judicial interventions) the database found 155 articles between 1971 and 2022 from which 110 were selected for analysis (57 are from Academic Search Complete, 28 from PsycInfo, 10 from Academic Search Ultimate, seven from Sociology Source Ultimate, four from Business Source Complete, two from Criminal Justice Abstracts, and two from PsycArticles); additional records were included trough manual search. From these studies, 23 articles were included, as they answered the research question, and therefore, constitute the final sample of this revision. The results indicate treatment as an effective response of the criminal justice system in the reduction of criminal recidivism and/or drug use, addressing the criminogenic effect of reclusion/imprisonment. Therefore, interventions that privilege treatment should be chosen, although there are still gaps in terms of evaluation, monitoring and scientific publications regarding the effectiveness of treatment in this population.